2015
DOI: 10.1007/s11684-015-0394-y
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary alveolar microlithiasis: an interesting case report with systematic review of Indian literature

Abstract: Pulmonary alveolar microlithiasis is a rare disease characterized by intra-alveolar presence of microliths. This study reports an interesting case of pulmonary alveolar microlithiasis and provides a systematic review of cases reported from India. A 23-year-old female presented with a history of cough, wheeze, chest pain, and episodic wheeze for five months. Pulmonary function tests demonstrated an obstructive pattern, and chest Xray showed fine micronodular opacities predominantly involving the middle and lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…Theoretically, this might be an advantage when developing cell therapies for solid organs like the lung where ossification should be avoided. In fact, calcification and bone formation, although not normally occurring in lung tissues, have been described in very rare conditions, such as pulmonary alveolar microlithiasis (PAM), diffuse pulmonary ossification (DPO) and ossification in carcinoid tumors 6 7 8 . Adult lung MSC secreted significantly higher amounts of the cytokine MCP-1, which is known to be important for innate immunity by attracting monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, this might be an advantage when developing cell therapies for solid organs like the lung where ossification should be avoided. In fact, calcification and bone formation, although not normally occurring in lung tissues, have been described in very rare conditions, such as pulmonary alveolar microlithiasis (PAM), diffuse pulmonary ossification (DPO) and ossification in carcinoid tumors 6 7 8 . Adult lung MSC secreted significantly higher amounts of the cytokine MCP-1, which is known to be important for innate immunity by attracting monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In general, steroid hormone therapy appears to be ineffective for PAM, though a few authors have reported subjective improvement in some patients 62,63 .…”
Section: Pharmacologic Treatment Optionsmentioning
confidence: 99%
“…Inhaled corticosteroid therapy does not appear to improve radiographical manifestations of PAM. It has been used effectively to treat symptoms and abnormal lung function in PAM patients who present with accompanying conditions such as spirometrically proven obstructive lung disease suggestive of asthma, lymphocytic interstitial pneumonitis and discoid lupus erythematosus among others [97][98][99], but there is little evidence to support routine inhaled corticosteroid use in patients with PAM.…”
Section: Inhaled Corticosteroidsmentioning
confidence: 99%